Representation of the concept “Traditional food” - García Barrón, Sergio Erick; Rivera Muñoz, Roberto Efraín; Camacho, David; Pérez Camarillo, Juan Pablo; Leyva Trinidad, Doris Arianna (Agrociencia Uruguay, 2022)
Foods fulfil social and nutritional functions. Knowing the meaning of foods is essential to understand the behavior towards them, especially when it comes to traditional foods. Two groups of people from Mezquital Valley and the Comarca Minera region in Hidalgo, Mexico, were interviewed through word association to find out what words they associated with the concept of "traditional food". The results were analyzed using the Latent Semantic Analysis (LSA). Through the LSA, nine dimensions were found for the Mezquital Valley and seven for the Comarca Minera region. These were further reduced to three defining dimensions shared between regions: Nutrition and nutritional quality, Territorial identity of a region, and Experiences derived from consumption. The Food Culture dimension was typical of the Mezquital Valley. Our findings suggest that LSA is suitable for the analysis of concepts and that regions have dimensions of their own geocultural context.